Conditional Spaces : Hong Kong Lesbian Desires and Everyday Life - Tang, Denise Tse-Shang (Queer Asia., 2011)
This book offers an in-depth sociological study on Hong Kong lesbian and transgender lesbian subjectivities and their materialization within multiple spaces. Based on thirty life history interviews, the author attempts to map the complex relations between lesbian subjectivities and spatialities as they emerge, develop, interact and negotiate with each other in their everyday lives. Drawing upon theories on cultural studies, feminism, postcolonialism, urban sociology and queer theory, this book positions Hong Kong as a late capitalist city and neoliberal economy, to bring the notion of sexuality and spaces together in a theoretical exercise in order to focus on the forces that determine the conditions and possibilities for the materialization of lesbian and transgender lesbian desires and identities. Tang investigates social relations within certain spaces and make linkages between a living room, a busy street, a classroom, a church congregation, a workplace and a queer film festival. Hong Kong women with lesbian desires and transgender lesbians can be understood as exclusionary to some spaces but participatory in the constant development of new sites where their needs and intimate desires are met. Tang concludes that a preliminary analysis of spaces in Hong Kong can be rooted in a physical sense but also proposes conditional spatiality as a theoretical concept to understand the emergence and disappearance of spaces.